MSS-1 ～ MSS-2 (The Japanese Journal of SURGICAL METABOLISM and NUTRITION, 2017)
PURPOSE: To evaluate the validity and reliability of commercially available wearable heat stress monitors (HSM) for estimating core body temperature (Tc) in firefighters during exercise-induced hyperthermia and recovery while wearing firefighting personal protective equipment (PPE). METHODS: Twenty-one firefighters completed two identical laboratory trials consisting of treadmill exercise in PPE followed by seated recovery. Tc was measured continuously using rectal thermometry (Trec) (criterion), a gastrointestinal telemetric pill alongside four wearable HSM (Equivital, Kenzen, Zephyr, CORE (arm and chest placement)). Validity was assessed using mean bias, 95 % limits of agreement (LoA), mean absolute error (MAE), root mean square error (RMSE), Pearson's r, Lin's concordance correlation coefficient (CCC), and the proportion of readings within ± 0.3 °C of Trec. Temperature-dependent error was examined across 0.5 °C Trec increments. Reliability was assessed using intraclass correlation coefficients (ICC) (2,1), test-retest bias, and LoA. RESULTS: All HSM demonstrated poor agreement (CCC = 0.26-0.85) along with wide LoA (1.25-2.22 °C) across all phases. During exercise, Equivital showed the strongest overall performance. During recovery, accuracy deteriorated markedly for all devices, with MAE and RMSE approximately doubling and fewer than one-third of readings fell within ± 0.3 °C of Trec. Temperature-dependent analyses revealed progressive increases in RMSE above ~38.5 °C, peaking during early recovery. When exercise and recovery were combined, Equivital and the CORE devices demonstrated the most favourable performance. Overall reliability was moderate to good (ICC = 0.74-0.81), with lower reproducibility for the arm-mounted devices (Kenzen and CORE-arm). CONCLUSIONS: Wearable HSM can track general trends in Tc but lack the accuracy and precision required for critical safety or return-to-work decision-making in firefighters, particularly at higher Tc and during recovery.